2016
DOI: 10.4236/ojcm.2016.64009
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Stability Properties of Medium Density Fibreboard (MDF) from Treated Oil Palm (<i>Elaeis guineensis</i>) Empty Fruit Bunches (EFB) Fibres

Abstract: The aim of the study was to investigate the effect of pre-treatments by using sodium hydroxide (NaOH) and acetic acid on oil palm Empty Fruit Bunch (EFB) fibres for the production of Medium Density Fibreboard (MDF). The EFB fibres were treated with chemicals in the concentration range of 0.2%, 0.4%, 0.6% and 0.8% prior to refining. Single-homogenous layer MDF with 12 mm thickness and density of 720 kg/m 3 was produced. Urea-Formaldehyde (UF) was applied at 10% loading (based on dry weight of dry fibres) as a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…Meanwhile, [8] has found that untreated composites of rattan particulate reinforced paper pulp, using starch as a binder, is better than alkali treated samples in water absorption. Chemical treatment has been reported as capable of removing hemicelluloses and lignin content of the plant fibre resulting in a reduction of water absorption and thickness swelling of the biocomposites [1,19]. This result agrees with this earlier finding as the BSF contains no wax and has higher amount of lignin and hemicelluloses than rice husk.…”
Section: Water Absorptivity and Thickness Swellingsupporting
confidence: 83%
See 3 more Smart Citations
“…Meanwhile, [8] has found that untreated composites of rattan particulate reinforced paper pulp, using starch as a binder, is better than alkali treated samples in water absorption. Chemical treatment has been reported as capable of removing hemicelluloses and lignin content of the plant fibre resulting in a reduction of water absorption and thickness swelling of the biocomposites [1,19]. This result agrees with this earlier finding as the BSF contains no wax and has higher amount of lignin and hemicelluloses than rice husk.…”
Section: Water Absorptivity and Thickness Swellingsupporting
confidence: 83%
“…It is essential to characterize the properties of composites produced from different materials sources to discern suitable blend or composition for specific applications. Chemical pre-treatment has been recommended for natural fibres used in composites to enhance the removal of hemicelluloses constituents, which are hydrophilic and often responsible for high thickness swelling and water absorptivity of the resulting composites [1]. Meanwhile, binders are important components in composites matrix.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, natural fibre is known as a reinforcement material in polymer composite, due to the environmental concerns by substituting synthetic or man-made fibres. Natural fibre reinforced polymer composite (NFRPC) is a composite material made up of a polymer matrix mixed with natural fibres, such as oil palm [1], jute [2,3], flax [4], banana fibre [5], kenaf [6,7] ramie [8]. These fibres are widely used as reinforcements in the NFRPC because they are low in density, good in mechanical properties, recyclable, and well in terms of strength per weight materials [9,10].…”
Section: Introductionmentioning
confidence: 99%